Walking the talk: Using digital media to develop distance learners' digital citizenship at the Open University (UK). Issue 3 (3rd July 2018) - Clough, Helen; Closier, Amanda
ABSTRACT: This article describes the approaches that the Library at the Open University has taken to ensure that distance learning students develop digital and information literacy skills for study, work and lifelong learning. Librarians create learning objects and work with academics to embed them into the online curriculum. They also deliver a program of live online training and pilot new approaches to engage with the student community.